FORMULATION AND EVALUATION OF TOPICAL ANTIFUNGAL GEL CONTAINING ITRACONAZOLE - Kasar, Poonam Madhukar; Kale, Kalyanisundarrao; Phadtare, Dipti Ganesh (International Journal of Current Pharmaceutical Research, 2018)
Objective: The present research has been undertaken with the aim to develop a topical gel formulation of Itraconazole. Itraconazole is an imidazole derivative and used for the treatment of local and systemic fungal infection. The oral use of Itraconazole is not much recommended as it has many side effects. Commercially Itraconazole topical gel preparation are not available in the market, thus this formulation is made for better patient compliance and to reduce the dose of the drug and to avoid the side effects like liver damage and kidney damage. Methods: The gel was formulated by changing the polymer ratio. Various formulation (F1, F2, F3, F4, F5) were developed by using a suitable polymer (carbopol 934p and HPMC). The formulation was evaluated for % yield, spreadability, extrudability, wash ability and viscosity in vitro drug release study, skin irritation study, stability testing. Results: Viscosity studies of various formulations revealed that formulation F3 was better to compare to others. From among all the developed formulation, F3 shows better drug diffusion, did good Rheological properties. pH of the F3 formulation is sufficient enough to treat the skin infections. Results indicated that the concentration of carbopol-934 and HPMC K4M significantly affects drug release and rheological properties of the gels. Conclusion: It was concluded that formulation F3 was the best formulation among this formulation. Hence formulation F3 should be further developed for scale-up to industrial production.